Karakteristik Spiritual Leadership dalam Tafsir Qs. Al-Maidah Ayat 8 - Nadilla Aleyda Maqhfira Agustin; Miftah Farid; Ahmad Syawal; Muhamad Iqbal Wibisono; Muhammad Anas Kamaluddin (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to describe the characteristics of spiritual leadership in the interpretation of Qs. Al-Maidah verse 8. A qualitative-descriptive approach is used in this study and the type of research conducted is library research. The findings obtained are essentially in the Islamic perspective, leadership is a sacred responsibility mandate carried out by individuals to direct themselves, others, and even society as a whole towards shirathal mustaqim based on the principles of Islamic teachings. In Qs. Al-Maidah verse 8, believers are ordered to carry out their work carefully, honestly and sincerely because of Allah, both religious and worldly affairs. Thus, the characteristics of spiritual leadership in Qs. Al-Maidah verse 8 include: (1) upholding justice because of Allah, (2) not being driven by hatred, (3) honesty, (4) being pious to Allah, and (5) being aware of Allah's supervision.